The Effect of Flexible Small Groups on Math Achievement in First Grade - David Benders; Tracy Craft (Networks: An Online Journal for Teacher Research, 2016)
This action research study explores the Guided Math Approach to improving math scores for first grade students. Previous MAP (Measure of Academic Progress) scores were used to measure proficiency and students were placed in separate categories for appropriate instruction. This study reviewed math achievement scores on MAP test from a First grade classroom in a rural area of southern Kentucky. The results from this study reflect an improvement in student mathematical knowledge and achievement of eleven below level students in the Math concept “Telling Time to the Hour and Half-hour” as required by Common Core Standard. All students received instruction within flexible grouping rotation of one hour and fifteen minute blocks. Below level students were extracted during instruction time and grouped to provide small group instruction in cooperation and individual work. The smaller group instruction is guided by the teachers to address deficiency areas identified within the pre-test assessment. The analysis revealed one hundred percent proficiency in the instructional lesson used for this study. The finding support the potential benefits and continuous need to explore the benefits of Guided math approach for student achievement in math.
Keywords: action research; math education; first grade; flexible grouping; mathematics